Health-Seeking Behavior and Delay in Diagnosis of Tuberculosis - Nasution, Helmi Suryani; Reskiaddin, La Ode; Sari, Puspita; Syukri, Muhammad (Politeknik Kesehatan Kemenkes Mamuju, 2024)
Indonesia ranks as the second largest country in terms of the number of tuberculosis (TB) cases. It is estimated that approximately 33% of TB cases remain undiagnosed and unreported. Identifying a health-seeking behavior including diagnostic delay in Jambi Municipality is necessary to increase tuberculosis (TB) case finding. This study aims to identify health-seeking behavior, calculate diagnostic delay, and identify factors associated with diagnostic delay, namely individual, social, and structural aspects among TB cases. This study used a cross-sectional design among bacteriologically confirmed pulmonary TB cases with a new treatment history in Jambi Municipality. The number of participating samples was 135 people with multi-stage random sampling. This study revealed that the most common health-seeking behaviors among TB cases were visiting drug stores/pharmacies (20.7%) and community health centers (CHCs) (20.0%). Diagnostic delay was experienced by 75.7% of TB cases with a median of 48 days and an interquartile range of 22-107 days. Variables associated with diagnostic delay were being unmarried (aOR 0.3, 95%CI 0.1-0.9, p = 0.031), moderate social support (aOR 0.2, 95%CI 0.1-0.6, p = 0.004), visit drugstore/pharmacy after symptom onset (aOR 8, 2, 95%CI 1.6-42.3, p = 0.012), the number of health facility visits made before diagnosis was 2-6 (aOR 3.1, 95%CI 1.1-9.3, p = 0.039), and TB stigma from the community perspective was high (aOR 0.3, 95%CI 0.1-0.8, p = 0.019). Evaluation of public-private mix (PPM) activities, especially those involving pharmacies/drug stores and private health facilities, and evaluation of TB screening at CHCs need to be considered. Massive education, community involvement, and psychosocial support are also needed to prevent delays in TB diagnosis.